# Boolean logic

Discussion in 'Homework Help' started by dagarve, Nov 4, 2006.

1. ### dagarve Thread Starter New Member

Nov 4, 2006
1
0
need help:

how do I simplify this equation. AB+(-A-BC). -A & -B means not A and Not B.

2. ### Papabravo Expert

Feb 24, 2006
10,338
1,850
As written it is ambiguous. Does -BC mean "not B and C" or does it mean "not (B and C). You can either use parentheses or transform the expression to reverse Polish notation.

3. ### Papabravo Expert

Feb 24, 2006
10,338
1,850
Rewriting the expression with parentheses as AB + (-A-B)C
This expression is already in minimal form. There are no common factors, and thus there is no simplification. Why do you think that there is?

4. ### Dave Retired Moderator

Nov 17, 2003
6,960
145
If I'm not mistaken, rewriting the expression with parentheses as AB + (-A-(BC)), it is also in minimal form (consider the expression using DeMorgans theorum).

With only one of exach term I don't see how this can be simplified.

Dave

5. ### vikram_kumar New Member

Nov 2, 2006
3
0
AB+(-A-BC). -A & -B means not A and Not B

IF expression
(1)
AB+A'+(BC)' (use "(XY)'=X'+Y' " )
=AB+A'+B'+C'; (use "X+X'Y=X+Y" )
=A'+(B+B')+C'; (USE"X+X'=1")
=A'+1+C' (USE"1+X=1")
=1

IF expression
(2)AB+A'+B'C
=AB+A'+B'C; (use "X+X'Y=X+Y" )
=A'+B+B'C'; (use "X+X'Y=X+Y" )
=A'+B+C' ;

6. ### Papabravo Expert

Feb 24, 2006
10,338
1,850
I think you copied the original expression incorrectly. There are only two terms, not three.